Engineered landscapes of the southern Murray–Darling Basin: Anthropocene archaeology in Australia. (December 2019) - Davies, Peter; Lawrence, Susan
Human activities over the past 200 years have fundamentally transformed the shape of Australia's southern Murray–Darling Basin. The arrival of British colonists in the 19th century disrupted millennia of human management of the region and brought widespread changes to biota and soils. The subsequent development of mining, transport and irrigation infrastructure re-engineered the region's landscapes to meet human objectives and ambitions. This article offers an integrated regional history of anthropogenic change across the southern Murray–Darling Basin, identifying historical processes driving complex ongoing interactions between human activities and the natural environment. We examine three broad domains of engineering and geo-disturbance in the region, including the development of transport corridors, micro- and macro-scale water management and landforms remade by erosion and sedimentation. We use the archaeology of the recent past to integrate insights drawn from physical geography, fluvial geomorphology and related research into the enduring landscape changes of modern Australia's food bowl.